Foreign Migrants Trespassing in Sabah Forest Reserves: A Legal Discourse - Rohani Abdul Rahim; Muhammad Afiq Ahmad Tajuddin; Rovina Intung; Azizah Landa; Herlina Makanah (Faculty of Law, Sriwijaya University, Indonesia, 2021)
According to Sabah Forestry Enactment 1968, Yang di-Pertua Negeri Sabah is given the power to reserves forests for various purposes including commercial, protection, domestic and others. Sabah Forestry Department is entrusted with proper and efficient planning, and implementation of State forest resources management (SFM) to comply with the sustainable forest principles. It achieves to manage forest resources towards sustainable and profitable forest governance. However, Sabah forest reserves were threatened by illegal trespassing by foreign migrants to possess forest produce unlawfully and to occupy State land illegally. This article aims to expose the causes of the invasion of forest reserves by foreign migrants, the offences committed by foreign migrant activities in the forest reserves, violation of specific legislation such as the Immigration Act 1959/63 and the Forest Enactment 1968. The qualitative legal research methodology was used to understand the issues at hand, the existing applicable laws and the legal implications for such illegal activities in these forest reserves. Secondary data found in the legislation, journals, annual report, and law publication were collected, reviewed, analysed, and discussed to understand its legal implications better. Thus, efforts to expose these illegal activities by foreign migrants is essential to ensure Sabah Forest Reserves can continuously be maintained and not destroyed at the hand of illegal foreign trespassers. Employers should also be made responsible for their involvement in trafficked or smuggled illegal migrants as workers and simultaneously, conduct illegal activities to deceit the State Forestry efforts and developmental planning in Sabah.